PENDEKATAN VALUASI HAK CIPTA DALAM SKEMA JAMINAN FIDUSIA - Nindya, Astri Rizky; Siswoyo, Amelia Anggriany (Lex Lectio Law Journal, 2025)
AbstractThe valuation of copyright as a fiduciary collateral asset is a critical component in the development of intellectual property-based financing schemes. As an intangible asset, copyright possesses unique characteristics that differentiate it from conventional forms of collateral, requiring structured, measurable, and accountable valuation approaches. This article explores the valuation mechanisms of copyright by examining internationally recognized methods such as the cost approach, market approach, and income approach. Using a normative legal method, this study analyzes the relevant Indonesian legal framework, including the Copyright Law, the Fiduciary Security Law, and Government Regulation No. 24 of 2022 on the Creative Economy. The findings indicate that, although there is a legal foundation for using copyright as collateral, the absence of national valuation standards and specialized appraisal institutions remains a major obstacle. Therefore, regulatory reform and the establishment of accredited intellectual property appraisers are essential to ensure the legality, objectivity, and financial viability of copyright-based fiduciary guarantees.AbstrakValuasi hak cipta sebagai objek jaminan fidusia merupakan elemen fundamental dalam menjamin keberlangsungan transaksi pembiayaan berbasis kekayaan intelektual. Hak cipta yang bersifat tidak berwujud memerlukan metode penilaian yang berbeda dari aset konvensional, dan pendekatan yang lazim digunakan adalah pendekatan biaya, pasar, dan pendapatan. Penilaian ini menjadi dasar bagi lembaga keuangan dalam menentukan besaran kredit yang layak diberikan dan memitigasi risiko gagal bayar. Meskipun kerangka hukum di Indonesia telah membuka ruang hukum bagi pemanfaatan hak cipta sebagai jaminan fidusia, hambatan utama masih terletak pada belum tersedianya standar valuasi nasional dan lembaga penilai khusus yang kompeten di bidang kekayaan intelektual. Untuk itu, dibutuhkan sinkronisasi regulasi, peningkatan kapasitas institusi appraisal, serta penyusunan pedoman teknis valuasi yang dapat diadopsi oleh sektor keuangan, guna menjadikan hak cipta sebagai agunan yang kredibel dan berdaya guna dalam sistem pembiayaan nasional.